Report of the Study Team on District Administration - Administrative Reforms Commission (Administrative Reforms Commission, Government of India)
The Administrative Reforms Commission on 17th July, 1966, appointed a Study Team on District Administration. The Study Team was asked to ascertain facts, locate the principal problem areas, examine solutions for the problems and suggest such of them as they would recommend for the Commission’s considerations. In its resolution of the 5lh January, 1966, the Government of India set up a Commission of Inquiry to examine the public administration of the country and make recommendations for reform and reorganisation where necessary. The Commission was asked to give consideration to the need for ensuring the highest standards of efficiency and integrity in the public services and for making public administration a fit instrument for carrying out the social and economic policies of the Government and achieving social and economic goals of development, as also an administration which is responsive to the people. It was asked to consider in particular ten aspects of the administration including district administration. The main issues to be examined under district administration were listed in the Schedule to the Resolution.
Administrative Reforms Commission